Habu coagulotoxicity: Clinical implications of the functional diversification of Protobothrops snake venoms upon blood clotting factors. (March 2019) - Debono, Jordan; Bos, Mettine H.A.; Nouwens, Amanda; Ge, Lilin; Frank, Nathaniel; Kwok, Hang Fai; Fry, Bryan G.
Abstract: Venom can affect any part of the body reachable via the bloodstream. Toxins which specifically act upon the coagulation cascade do so either by anticoagulant or procoagulant mechanisms. Here we investigated the coagulotoxic effects of six species within the medically important pit viper genus Protobothrops (Habu) from the Chinese mainland and Japanese islands, a genus known to produce hemorrhagic shock in envenomed patients. Differential coagulotoxicity was revealed: P. jerdonii and P. mangshanensis produced an overall net anticoagulant effect through the pseudo-procoagulant clotting of fibrinogen; P. flavoviridis and P. tokarensis exhibit a strong anticoagulant activity through the destructive cleavage of fibrinogen; and while P. elegans and P. mucrosquamatus both cleaved the A-alpha and B-beta chains of fibrinogen they did not exhibit strong anticoagulant activity. These variations in coagulant properties were congruent with phylogeny, with the closest relatives exhibiting similar venom effects in their action upon fibrinogen. Ancestral state reconstruction indicated that anticoagulation mediated by pseudo-procoagulant cleavage of fibrinogen is the basal state, while anticoagulation produced by destructive cleavage of fibrinogen is the derived state within this genus. This is the first in depth study of its kind highlighting extreme enzymatic variability, functional diversification and clotting diversification within one genus surrounding one target site, governed by variability in co-factor dependency. The documentation that the same net overall function, anticoagulation, is mediated by differential underlying mechanics suggests limited antivenom cross-reactivity, although this must be tested in future work. These results add to the body of knowledge necessary to inform clinical management of the envenomed patient.